Strengthening Character Through Learning Of BAM Of Minang Language For Elementary School Students (JED (Jurnal Etika Demokrasi), 2021)
Essential education is to develop a whole person that is a good and characterful human being. The developed character values already exist in Minangkabau culture and customs. The customary philosophy of basandi syarak, the basandi syarak is the basis for the formation of character in culture and customs. Minang language is a form of local wisdom that must be continuously preserved and used in BAM local content learning activities. The Minang language is a communication tool in teaching traditional and cultural values in BAM learning. This study aims to determine the level of student understanding and reinforcement of character by teaching BAM in the Minangkabau language. The research method used is descriptive qualitative method. Where the approach in this study is carried out intensively, in depth, in detail, and comprehensive when PBM subjects natural cultural minangkabau. Data collection techniques in this study were interviews (interviews), observation, and documentation. Based on the results of research conducted shows that by teaching local content BAM in the Minang language is able to strengthen the character of students, Minang language as the mother tongue is easier to understand and comprehend by students, especially those related to expressions, rhymes and proverbs as well as the implementation of politeness as individuals in the family and society.Pendidikan esensinya adalah membangun manusia seutuhnya yaitu manusia yang baik dan  berkarakter, Nilai karakter yang dikembangkan telah ada dalam budaya dan adat istiadat Minangkabau. Falsafah adat basandi syarak, syarak basandi kitabulah menjadi dasar pembentukan karakter pada budaya dan adat istiadat.  Bahasa minang merupakan salah satu bentuk kearifan lokal harus terus dilestarikan dan dipergunakan dalam kegiatan pembelajaran muatan lokal BAM. Bahasa Minang menjadi alat komunikasi dalam mengajarkan nilai nilai adat dan budaya pada pembelajaran BAM. Penelitian ini bertujuan untuk mengetahui tingkat pemahaman siswa serta penguatan karakter dengan mengajarkan BAM berbahasa Minangkabau. Metode penelitian yang digunakan ini adalah metode kualitatif deskriptif. Dimana pendekatan dalam penelitian ini  dilakukan secara intensif, mendalam, mendetail, dan komperhensif pada saat PBM mata pelajaran budaya alam minangkabau.  Teknik pengumpulan data dalam penelitian ini adalah wawancara (interview), observasi, dan dokumentasi. Berdasarkan hasil penelitian yang dilakukan menunjukkan bahwa  dengan mengajarkan muatan lokal BAM dalam bahasa Minang mampu memperkuat karakter siswa, Bahasa Minang sebagai bahasa ibu lebih mudah difahami dan dimengerti oleh siswa terutama yang berkaitan dengan ungkapan, pantun dan pepatah petitih serta implementasi adab dan sopan santun sebagai individu dalam keluarga dan masyarakat.